Predictors of Parenchymal Hematoma After Mechanical Thrombectomy: A Multicenter Study. Issue 9 (September 2019) - Boisseau, William; Fahed, Robert; Lapergue, Bertrand; Desilles, Jean-Philippe; Zuber, Kevin; Khoury, Naim; Garcia, Jeanne; Maïer, Benjamin; Redjem, Hocine; Ciccio, Gabriele; Smajda, Stanislas; Escalard, Simon; et al.
Abstract : Background and Purpose—: Parenchymal hematoma (PH) is a rare but dreadful complication of acute ischemic stroke with unclear underlying mechanisms. We aimed to study the incidence and predictors of PH after mechanical thrombectomy. Methods—: Data from a prospective observational multicenter registry was screened to identify acute ischemic stroke patients with an anterior circulation large vessel occlusion who underwent mechanical thrombectomy. Clinical, imaging, and procedural characteristics were used for the analysis, including brain imaging systematically performed at 24 hours. PH occurrence was assessed according to ECASS (European Collaborative Acute Stroke Study) criteria. Univariate and multivariable analyses were performed to identify predictors of PH. Results—: A total of 1316 patients were included in the study. PH occurred in 153 out of 1316 patients (11.6%) and was associated with a lower rate of favorable outcome and increased mortality. On multivariable analysis, age (per 1 year increase, odds ratio [OR], 1.01; 95% CI, 1.00–1.03; P =0.05), current smoking (OR, 2.02; 95% CI, 1.32–3.09; P <0.01), admission Alberta Stroke Program Early CT Score (per a decrease of 1 point, OR, 1.70; 95% CI, 1.18–2.44; P <0.01), general anesthesia (OR, 1.98; 95% CI, 1.36–2.90; P <0.001), angiographic poor collaterals (OR, 2.13; 95% CI, 1.36–3.33; P <0.001) and embolization in new territory (OR, 2.94; 95% CI, 1.70–5.10; P <0.001) were identified as independent predictors of PH. Conclusions—: PH occurred at a rate of 11.6% after mechanical thrombectomy, with high morbidity and mortality. Our study identified clinical, radiological, and procedural predictors of PH occurrence that can serve as the focus of future periprocedural management studies with the aim of reducing its occurrence. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03776877. Abstract : Supplemental Digital Content is available in the text.